Eco-friendly and modern methods of waste recycling for enhancing farm profitability - ACHAB Oumhani; AZZA Nadjoua; DJERRAYA Rahma (Université of Eloued, 2024)
ACHAB Oumhani; AZZA Nadjoua; DJERRAYA Rahma . Eco-friendly and modern methods of waste recycling for enhancing farm profitability .masters, 2024. Department of cellular and molecular biology. Faculty of Nature and Life Sciences. University of El-Oued. [consulted in ../../….]. Available at. [copy the link here].
Keywords: Eco-friendly and modern methods of waste recycling for enhancing farm profitability